Study on the coupling and coordination relationship between the digital economy and green development: evidence from Guangdong province in China - Zhong, Xiaojun; Cao, Zhiyi; Peng, Bo; Cheong, Tsun Se (Frontiers in Environmental Science, 2023)
The digital economy city and green development of China are important engines with important backgrounds. This paper takes 21 prefecture-level cities in Guangdong Province as the research object. By constructing the index system of the digital economy and green development, this paper discusses the external spatial pattern and internal temporal evolution characteristics of the coordinated development of the digital economy and green development from the two perspectives of intercity and inner city. The results show that: (1) From the perspective of intercity, there is a large gap between the development level of the digital economy and the green development level of all cities, only Guangzhou and Shenzhen have the digital economy development level ahead of the green development level. The coupling level of the two systems presents an unbalanced pattern of "centre-edge", and "Guangzhou-Foshan-Shenzhen-Dongguan" becomes the core pole of the coupling development of the two systems in the province. The coordinated horizontal cascade distribution of the two systems is obvious, showing a spatial pattern of decreasing step by step from the first circle to the third circle. (2) From the perspective of inner city, the digital economy level and green development level of all cities showed an upward trend from 2013 to 2019. The coupling level shows a two-stage development trend: the stable development stage from 2013 to 2016, and he accelerated development stage from 2016 to 2019, and the internal interaction of the two systems is deepening.The coordination level of all cities improved significantly in seven years, and in 2019, 21 cities all reached the level of moderate coordination or high coordination. Based on above research conclusions, in order to promote the positive interaction between digital economy and green development, this paper proposes to optimize resource allocation based on regional differences, and adhere to innovation-driven policy proposals to activate the potential of green development.